CAD_TOOL (CAGE AQUACULTURE DECISION SUPPORT TOOL) PERANGKAT PENDUKUNG KEPUTUSAN DALAM BUDIDAYA KERAMBA JARING APUNG - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2008)
CADS_TOOL is a software decision support tool for floating net cages management which constructs of two elemens, software and technic module. It has been developed by the copyright holders (the Australian Centre of International Agriculture Research (“ACIAR”), the Australian Institute of Marine Science (“AIMS”) and the Departemen Kelautan dan Perikanan (“DKP” : Ministry of Marine Affairs and Fisheries, Indonesia)as a tool. The objective of this software is to classify a site, to select the best site from several site alternatives, to calculate the sustainable holding density of a chosen site and to perform a basic economic appraisal of a farm at that site. CADS_TOOL includes 4 models for calculating holding or carrying capacity as sub-tabs under the Holding Capacity tab. For marine cages, the methods used are: Simplified MOM based on Stigebrandt et al., (2004), Tookwinas et al. (2004) and Hanafi et al. (2006), while Pulatsü et al. (2003) is used for freshwater cages in lakes/dams. In this paper will describe only a Tookwinas model.